Rôle de la glace saisonnière dans la dynamique de l'écosystème marin de l'Antarctique : impact potentiel du changement climatique global - Gustavo Ferreyra (Éditions en environnement VertigO, 2004)
Seasonal ice cover is linked to an intense biological activity in polar regions. Every year, ice melting induces the stabilisation of the water column which can be observed until 150 km from the margin of seasonal ice, favoring the development of profuse phytoplankton blooms. For the case of Antarctica, life cycles of key species in the ecosystem, particularly the krill Euphausia superba, strongly depends on ice dynamics. This species has been considered as the main link between phytoplankton and higher trophic levels in the food web (fishes, birds and mammals). Several field observations as well as models suggest a replacement of krill by another group of organisms: the salps (particularly Salpa thompsoni). Such replacement has been related to the decrease in duration and extent of seasonal ice during the last decades, which in turn shows a strong correlation with the air temperature increase in some areas of Antarctica (Amundsen – Bellingshausen seas and Antarctic Peninsula). These changes could have significant consequences for both the biodiversity and the functioning of the Antarctic ecosystem, since salps represent a low energy source for high predators. The potential significance of the above processes on Antarctic ecosystem dynamics is analysed in the present paper.